Secondary IOL Implantation - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2008)
In this issue of PJO there is excellent coverage of cataract surgery related options like secondary IOL implantation and particularly scleral fixation of IOL. Cataract treatment now is synonymous with cataract extraction with IOL implantation, be it primary or secondary. The choicest procedure is IOL in the bag. In certain situations in the bag insertion is not possible and one has to resort to anterior chamber (AC) insertion or scleral fixation of IOL. We all know the complications of AC IOL’s especially UGH syndrome etc. and also we are aware of demanding techniques and complications of scleral IOL fixations in the past.